BAHASA JAWA SEBAGAI IDENTITAS GENERASI MUDA MASYARAKAT PENDATANG DARI JAWA DI MERAUKE - Hanova Rani Eka Retnaningtyas (Haluan Sastra Budaya, 2023)
The Javanese ethnic community is widespread throughout the archipelago, although it is not well-known as an ethnic group that likes to wander. One of the places that later became the new residence of this ethnic group was the city of Merauke in Papua. The area at the easternmost tip of Indonesia. Far from the area of origin and have never even been to the island of Java, it is common for the Javanese people who live in Merauke to live. This can be a factor causing the weakening of the "Javanese" of the Javanese ethnic community in Merauke, especially the younger generation. Based on this hypothesis, this research was conducted to find out how the Javanese people use the Javanese language in Merauke. This research is qualitative. Researchers used a questionnaire in the form of open and closed questions to collect data. The population of this study was students of Javanese ethnicity, Musamus University, Merauke. Based on the data found by the researchers, it can be seen that the younger generation of Javanese living in Merauke has a low level of mastery of the Javanese language, especially the Javanese Kromo language.